Perancangan Media Praktikum Elektronika Digital Berbasis Virtual - Hendra Jaya (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2013)
The purpose of this study: 1) Develop a model-based virtual laboratory to enhance and facilitate the practice of character education in the vocational school, 2) Designing virtual laboratory which can improve laboratory processes and facilitate character education at vocational students. The method of this research wereresearch development. Software development models implemented through engineering approach: analysis, design, implementation, and evaluation. Virtual–based Laboratorywere developed to facilitate character education. The results of the analysis, design, and implementation produces a virtual laboratory software accompanied by facilities for character building. Evaluationfor the content aspect by mean score of 4.5 (very good), laboratorydesign 4.4 (very good), display aspect 4.4 (very good ), virtual aspect 4.50 (very good), and programming aspects 4.2 (good).